1990
DOI: 10.1111/j.1471-4159.1990.tb04565.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Acetylcholine Release from Cortical Slices in Aged Rats: Investigations into Its Reversal by Phosphatidylserine

Abstract: The release of total acetylcholine (ACh) and [3H]ACh was investigated in electrically stimulated cortical slices prepared from 4- and 18-month-old male Wistar rats. The slices were prelabeled with [3H]choline ([3H]Ch) and perfused with Krebs solution containing physostigmine. Total ACh was measured and the nature of the tritium efflux identified by HPLC. The total tritium content in the slices at the end of the incubation period was half as great in the old as in young rats. A linear relationship was found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…After two further washings, the cells were collected in 140 jil of 0.014 M citrate buffer prewarmed at 100°Cand homogenized in a glass-glass homogenizer. ACh was determined in the homogenates after HPLC separation, following the method of Vannucchi et al (1990).…”
Section: Ach Determinationmentioning
confidence: 99%
“…After two further washings, the cells were collected in 140 jil of 0.014 M citrate buffer prewarmed at 100°Cand homogenized in a glass-glass homogenizer. ACh was determined in the homogenates after HPLC separation, following the method of Vannucchi et al (1990).…”
Section: Ach Determinationmentioning
confidence: 99%
“…Impairment in the ability to synthesize and release ACh has been consistently reported in aged rodent cortex (Vannucchi et al 1990). The activity of AChE, the degradative enzyme of cholinergic system, in the cerebral cortex of 90 weeks old control group decreased significantly compared to 7 weeks old control with significant increase in the K m .…”
Section: Discussionmentioning
confidence: 97%
“…The cholinergic innervation of the cerebral cortex has been extensively investigated because of its role in arousal, learning and memory (Bartus et al 1985;McCormick 1989McCormick , 1992Olton et al 1991;Voytko et al 1994). Studies in rodents have shown a consistent decline in cortical ACh synthesis and release during ageing (Gibson et al 1981;Araujo et al 1990;Vannucchi et al 1990). Also, memory decline during ageing has been extensively documented in rodents (Ingram et al 1981), nonhuman primates (Presty et al 1987), and humans (Rowe and Kahn 1987).…”
Section: Introductionmentioning
confidence: 96%
“…Impairment in the ability to synthesize and release ACh has been consistently reported in aged rodent cortex (e.g., refs. [7][8][9]. Electrophysiological experiments in the hippocampus of old rats showed impairment in neuronal response to local application of ACh (but not of glutamate) without consistent changes in receptor number (1).…”
mentioning
confidence: 95%
“…Although the aging process seems to impinge on several neurotransmitter systems, special emphasis has been placed on the role of the cortical cholinergic innervation in geriatric memory dysfunction (6). Studies in rodents have shown a consistent decline in cortical acetylcholine (ACh) synthesis and release during aging (7)(8)(9), although little or no change occurs in cortical choline acetyltransferase activity (1,8,6,10). Further, the cholinergic basal forebrain neurons that project to the cortex undergo an age-related decrease in size though their number is apparently not diminished (11).…”
mentioning
confidence: 99%